Doporučení pro podávání biologické terapie u idiopatických střevních zánětů: třetí, aktualizované vydání - Bortlík, Martin; Ďuricová, Dana; Kohout, Pavel; Konečný, Michal; Koželuhová, Jana; Novotný, Aleš; Zbořil, Vladimír; Prokopová, Lucie; Douda, Tomáš; Stehlík, Jiří; Shonová, Olga; Mareš, Karel; et al. (Gastroenterologie a hepatologie, 2016)
The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE „uniform requirements“ for biomedical papers. Submitted: 22. 1. 2016 Accepted: 8. 2. 2016
Keywords: Biological Therapy; biologická terapie; Male; monoklonální protilátky; pouchitis; Tumor Necrosis Factor-alpha; biosimilární léčivé přípravky; kožní manifestace; Inflammatory Bowel Diseases; Child; Pregnancy; Breast Feeding; těhotenství; dítě; Adult; Skin Manifestations; dospělí; mužské pohlaví; kojení; idiopatické střevní záněty; humanizované monoklonální protilátky; vakcinace; Antibodies, Monoclonal, Humanized; novorozenec; perioperační péče; lidé; ženské pohlaví; Humans; Biosimilar Pharmaceuticals; Infant, Newborn; Vaccination; TNF-alfa; Antibodies, Monoclonal; Female; Perioperative Care; Pouchitis